2013
DOI: 10.1007/s12017-013-8257-7
|View full text |Cite
|
Sign up to set email alerts
|

SUMO and Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by progressive cognitive decline and is the most common cause of dementia in the elderly. Histopathologically, AD features insoluble aggregates of two proteins in the brain, amyloid-β (Aβ) and the microtubule associated protein tau, both of which have been linked to the small ubiquitin-like modifier (SUMO). A large body of research has elucidated many of the molecular and cellular pathways that underlie AD, including those involving the abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 164 publications
(215 reference statements)
1
75
0
Order By: Relevance
“…SUMOylation is a post-translational modification process that regulates the functional properties of many proteins, among which several are implicated in neurodegenerative disease. Many proteins that have functions relevant to AD pathology have been identifi ed as SUMO substrates, including those involved in synaptic physiology, mitochondrial dynamics, and infl ammatory signaling [74] .Glycation of tau can occur via the non-enzymatic formation of advanced glycation end-products [75] . Tau can be glycated in vitro, resulting in a loss of microtubule binding.…”
mentioning
confidence: 99%
“…SUMOylation is a post-translational modification process that regulates the functional properties of many proteins, among which several are implicated in neurodegenerative disease. Many proteins that have functions relevant to AD pathology have been identifi ed as SUMO substrates, including those involved in synaptic physiology, mitochondrial dynamics, and infl ammatory signaling [74] .Glycation of tau can occur via the non-enzymatic formation of advanced glycation end-products [75] . Tau can be glycated in vitro, resulting in a loss of microtubule binding.…”
mentioning
confidence: 99%
“…A number of studies alluded to the presence of SUMO1 in amyloid plaques (Lee et al., 2013). We therefore used our mouse model to test this notion.…”
Section: Resultsmentioning
confidence: 99%
“…The role of SUMOylation is particularly interesting in the context of neurodegenerative disorders with deregulated proteostasis (Feligioni et al., 2015; Krumova & Weishaupt, 2013; Lee, Sakurai, Matsuzaki, Arancio & Fraser, 2013; Liebelt & Vertegaal, 2016). Notably, SUMOylation can regulate the solubility of various disease‐associated proteins (Krumova & Weishaupt, 2013; Lee et al., 2013; Shahpasandzadeh et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to ubiquitin, which mainly tags proteins for degradation, SUMOylation is important for the normal functions of proteins in the cell. However, over the past few years, several studies have indicated that SUMOylation also has a role in aging and neurodegenerative diseases, including AD (Table 1) [32,33].…”
Section: Protein Sumoylationmentioning
confidence: 99%